Exploring the impact of social media on political discourse: a case study of the Makassar mayoral election - Jufri; Aedah, Abd Rahman; Suarga, . (2024)
Social media has become a significant force in today's modern society, influencing several areas, including politics, education, the economy, and the spread of information. This study examines how social media platforms influence political discourse, focusing on the Makassar mayoral race. This study looks into how Twitter, a well-known social media site, encourages more user participation in communications related to the Makassar mayoral election. In light of the Makassar mayoral election, this study employs several approaches, including data collection, acquisition, consolidation, and analysis, to address topics that are becoming increasingly popular on social media. Election dynamics are examined using the naïve Bayes approach. To increase the accuracy and efficiency of text mining operations, especially in result validation, text clustering, and classification, the k-means algorithm and support vector machines (SVM) were used. A hybrid method is employed to combine the benefits of k-means, SVM, and naïve Bayes. This method seeks to thoroughly grasp how social media affects conversations about the mayoral race, offering insightful information to political scientists and practitioners. The research on the Makassar mayoral race explores the influence of social media on political communication, highlighting Twitter's influence and a hybrid algorithm for sentiment analysis. It indicates the importance of social media strategy in political campaigns, providing insights for decision-makers, parties, and the public and recommending future research in this dynamic field.